Fibromyalgia in patients with psoriatic arthritis: Relationship with enthesopathy, sleep, fatigue and quality of life - (:unkn) unknown (WILEY, 2021)
Objectives To evaluate the relationship of fibromyalgia with enthesopathy, sleep, fatigue and quality of life in patients with psoriatic arthritis. Methods The psoriatic arthritis patients according to CASPAR criteria were included in the study. The diagnosis of fibromyalgia was based on 2016 ACR criteria. Demographic and clinical parameters were noted. Disease activity and enthesopathy were evaluated with Disease Activity Score-28 (DAS-28) and Maastricht Ankylosing Spondylitis Enthesitis Score (MASES), respectively. Functional assessment scales in this study were Psoriatic Arthritis Quality of Life (PsAQoL), Pittsburgh Sleep Quality Index (PSQI), Multidimensional Assessment of Fatigue (MAF). Fibromyalgia Impact Questionnaire (FIQ) was used to assess the functional status of fibromyalgia. The Mann-Whitney U test and Spearman correlation coefficient (rho) were used. Hierarchical multiple regression analysis used to examine the differential contributions to FIQ score.P We enrolled 50 PsA patients (31 female, 19 male) with a mean age of 49.5 years (SD: 10.2) and mean disease duration 7.5 years (SD: 7.5). Thirty-two patients (64% of PsA patients) fulfilled ACR criteria for fibromyalgia. The mean scores of MASES, PSQI, MAF and PsAQoL were significantly higher in patients with fibromyalgia (P < .05). The correlations between FIQ and other functional parameters were as follows; MASES (rho = 0.71,P < .0005), PSQI (rho = 0.62,P < .0005), MAF (rho = 0.60,P < .0005), PsAQoL (rho = 0.61,P < .0005). A moderate correlation was existing between FIQ and DAS-28 (rho = 0.42,P = .03). Conclusions Coexistence of fibromyalgia in PsA patients is associated with the presence of enthesopathy, poor quality of life, sleep disturbance and fatigue.
Keywords: clinical aspects; fibromyalgia; psoriatic arthritis; regional pain syndromes; soft tissue rheumatism; MULTIDIMENSIONAL ASSESSMENT; WIDESPREAD PAIN; SEVERITY SCALE; SPONDYLOARTHRITIS; QUESTIONNAIRE; COMORBIDITY; RELIABILITY; VALIDITY; PROFILE; VERSION